Mutual Dynamics of Certain Types of Bitcoin: Data from Wavelet Coherence - Lyashenko, Vyacheslav; Bilotserkivskyi, Oleksandr; Pyvavar, Iryna; Kots, Hryhorii (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Unconventional methods of analysis are a good tool for studying new trends and phenomena. One of these objects of research is the cryptocurrency market. The paper shows the possibility and feasibility of applying the ideology of wavelets to analyze the dynamics of prices for cryptocurrencies. For this, the methodology of wavelet coherence is used. This methodology has been applied to various cryptocurrency pairs. The calculation results for real data are presented. It is shown that the results obtained agree with the theoretical conclusions and research results of other authors.